2015
DOI: 10.1111/scs.12265
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with preference for dying at home among terminally ill patients with cancer

Abstract: The study showed that socio-economic factors such as gender, level of income and size of community were associated with preference for dying at home. Hence, this study qualifies prior studies on preferences for end-of-life care and advocates for a more nuanced picture of the subject. Advocacy in end-of-life nursing recommends optimising active listening and communication skills striving towards more patients' preferences in all settings may be heard and fulfilled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
(31 reference statements)
0
22
1
6
Order By: Relevance
“…These findings are consistent with literature that has identified socioeconomic determinants that increase rates of preference for home death, including identifying as non-Hispanic white race [ 42 ], greater education level, greater income levels, greater awareness of advanced directives [ 43 ], and more supportive living arrangements [ 44 ]. These findings can be contrasted with earlier studies, which found that immigrant or direct descendants express a higher preference for home death [ 45 ] and a higher likelihood of dying at home [ 24 ]. Building on our findings, further research is needed to more completely characterize how socioeconomic factors influence preference for home death.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with literature that has identified socioeconomic determinants that increase rates of preference for home death, including identifying as non-Hispanic white race [ 42 ], greater education level, greater income levels, greater awareness of advanced directives [ 43 ], and more supportive living arrangements [ 44 ]. These findings can be contrasted with earlier studies, which found that immigrant or direct descendants express a higher preference for home death [ 45 ] and a higher likelihood of dying at home [ 24 ]. Building on our findings, further research is needed to more completely characterize how socioeconomic factors influence preference for home death.…”
Section: Discussioncontrasting
confidence: 99%
“…Perhaps autonomy represents a greater value for those with higher education and the house is perceived as a place of greater empowerment 31 . However, there are few studies that investigates the associations between preference for home death and level of education 32 . Previous research in Ibiza 33 and China 34 showed that low educational attainment is associated with a greater preference for death at home and those with higher attainment prefer to die in institutions 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A death at home has been considered as a significant outcome and a "good death" in a large body of research in end of life care [1] [2] [3] [4] [5] due to better quality of care [2] [6] and autonomy [3] [5] [6]. The main body of literature shows that people prefer to die at home [5] [7] [8] [9] irrespective of their health conditions and living arrangements prior to death [7] [8].…”
Section: Introductionmentioning
confidence: 99%